5m=3msquared

Simple and best practice solution for 5m=3msquared equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5m=3msquared equation:


Simplifying
5m = 3msquared

Solving
5m = 3ademqrsu

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3ademqrsu' to each side of the equation.
-3ademqrsu + 5m = 3ademqrsu + -3ademqrsu

Combine like terms: 3ademqrsu + -3ademqrsu = 0
-3ademqrsu + 5m = 0

Factor out the Greatest Common Factor (GCF), 'm'.
m(-3adeqrsu + 5) = 0

Subproblem 1

Set the factor 'm' equal to zero and attempt to solve: Simplifying m = 0 Solving m = 0 Move all terms containing m to the left, all other terms to the right. Simplifying m = 0

Subproblem 2

Set the factor '(-3adeqrsu + 5)' equal to zero and attempt to solve: Simplifying -3adeqrsu + 5 = 0 Reorder the terms: 5 + -3adeqrsu = 0 Solving 5 + -3adeqrsu = 0 Move all terms containing m to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3adeqrsu = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3adeqrsu = 0 + -5 -3adeqrsu = 0 + -5 Combine like terms: 0 + -5 = -5 -3adeqrsu = -5 Add '3adeqrsu' to each side of the equation. -3adeqrsu + 3adeqrsu = -5 + 3adeqrsu Combine like terms: -3adeqrsu + 3adeqrsu = 0 0 = -5 + 3adeqrsu Simplifying 0 = -5 + 3adeqrsu The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

m = {0}

See similar equations:

| 4x-2=5x+11 | | r^3+24r-160=0 | | .2x+x^2=.99 | | 3t^2+23t-8=o | | 8+10x=26+x | | 0.06x=1730 | | 2X+3X+4=what | | .04+.4x+x^2=1 | | 2(3x+8)=5(x-7) | | q=8p-45 | | 42y+5=71 | | 11x-17=8x+9 | | 12x+3-6x-3=90 | | 9q+54=3q+90 | | 8+2b=10 | | 4j-4=2j+20 | | 3[5-4(4-c)]-5=5[3(5c-4)+2]-26 | | -6+y^2=10 | | x^2+.4x=.96 | | -2x^2+8x-56=0 | | 6x-9=x-4 | | -8+2a=-4 | | Y-25=-3(x-(-7)) | | 2x/3x-5/6 | | 2x^2-8x-56=0 | | 7x-2=-58 | | 5=7n-2 | | 3(x-10)-4=-6x-2 | | x-17=-12 | | -1=11+n | | 9x-13=-10+12x | | 9x-13=-10+12z |

Equations solver categories